131 Dynamic Magnetic Resonance Imaging Parameters for Objective Assessment of the Magnitude of Tethered Cord Syndrome in Patients With Spinal Dysraphism. Issue Volume 65:Issue CN(2018)Supplement 1 (16th August 2018) - Singh, Suyash; Behari, Sanjay; Bhaisora, Kamlesh S; Phadke, Rajendra V
Abstract: INTRODUCTION: Dynamic magnetic resonance imaging (MRI)-based criteria for diagnosing magnitude of tethered cord syndrome (TCS) in occult spinal dysraphism are proposed. METHODS: In this prospective, case-control design study, MRI lumbosacral spine was performed in 51 subjects [pilot group (n = 10) without TCS; control group (n = 10) without TCS; and, study group (n = 31) with spinal dysraphism (thick filum terminale [n = 12]; lumbar/lumbosacral meningomyelocoele [n = 6]; and lipomyelomeningocoele [n = 13]). The parameters compared in control and study groups included oscillatory frequency (OF), difference in ratio, in supine/prone position, of distance between posterior margin of vertebral body and anterior margin of spinal cord (oscillatory distance), with canal diameter, at the level of conus as well as superior border of contiguous 2 vertebrae above that level; delta bending angle (?BA), difference, in supine/prone position, of angle between longitudinal axis of conus and that of lower spinal cord; and, sagittal and axial root angles, subtended between exiting ventral nerve roots and longitudinal axis of cord were assessed. An outcome assessment at follow-up was done. RESULTS: In the study group (cord tethered), significantly less movement at the level of conus (OF0, P = .013) and one level above (OF1, P = .03), and significant difference in ? BA ( P = .0), were observed in supine and prone positions, compared to controls. Ventral nerve root stretching resulted in sagittal/axial root angle changes. Median OF (0.04) in the lipomyelomeningocoele group and group with thick filum terminale or meningomyelocele was significantly less than that in control group (0.23). Difference in median sagittal and axial root angles among study and control groups was statistically significant ( P = .00). CONCLUSION: New dynamic MRI-based parameters to establish the presence and magnitude of TCS have been defined. OF measured extent of loss of translational cord displacement in supine and prone positions; ? BA defined the relative angulation of conus with lower spinal cord; and sagittal and axial root angles represented ventral nerve root stretching.